Enzymatic synthesis of ω-3 fatty acids-based structured phospholipids: a novel solvent-free preparation approach and its catalytic mechanism - Wu, Yuxin; Peng, Xianwu; Lee, Yee-Ying; Xie, Pengkai; Tan, Chin-Ping; Wang, Yong; Zhang, Zhen (Elsevier, 2024)
ω-3 fatty acids-based phospholipids (ω-3-PLs) exhibit higher bioavailability within organisms and stability compared to polyunsaturated fatty acids in their neutral forms. In this study, ω-3 fatty acids enriched partial acylglycerols (ω-3-AGs) were produced from hydrolysis of algal oil firstly. The effects of hydrolysis processing parameters such as enzyme type, enzyme loading, oil-water ratio, reaction temperature, and time were evaluated. Subsequently, ω-3-PLs were prepared via interesterification of ω-3-AGs with PLs catalyzed by PLA1. When monoacylglycerols (MAGs) reached 60% in partial acylglycerols, the interesterification reaction showed a marked improvement, leading to the achievement of the optimal final ω-3-PLs content of 38.93%. Using molecular docking techniques to speculate on the catalytic mechanism, the results indicate that MAGs exhibit an affinity of up to −6.33 kcal/mol with PLA1, verifying their critical role in the interesterification process.